Desenvolvimento e criação de uma nova prática de trabalho em uma instituição de ensino superior: um estudo da aprendizagem e da mudança sob a perspectiva da teoria social de Schatzki - Rolon, Vanessa Estela Kotovicz (2016)
The goal of this thesis was to investigate how the teachers of a higher educational institution (IES) located in the city of Curitiba implemented a new educational practice though the innovative teaching method of the inverted classroom. We seek to understand how the teachers executed this project through their daily praxis as they conducted the change in the teaching method. The analytical unit is the social practice which was analyzed through the perspective of the Theory of Social Practice of Theodore Schatzki (2001; 2002; 2005; 2006; 2012). Therefore, we search to identify the constitutive elements of practice according to the cited author, which are the doings, the sayings, the rules, the teleoaffectivity, the practical understanding and the general understanding of a specific practice. The present research is inscribed in the Practice Based Studies (EBP) that are studies based in people’s every day’s activities as they develop practice. Although these studies have advanced considerably these past years, in Brazil there is still little research regarding this subject, as Bispo (2013) observes, since most of the publications are of European authors. The ethnographic method made it possible to map the group’s learning process while unfolding the practice. The goal was to understand the relationships developed among the participants of the group in their daily actions. We observed that these relationships where constructed in the daily routine of the group of teachers who searched for a consensus about what is reasonable for the participants of the new practice to do. This way, they created new knowledge since “as the subjects talk and act the produce and define their world” (GUBER, 2001, pg.45). We identified the development of a new practice in the workplace, and that group learning took place whereas a conscience, a memory of the project, allowed newcomers to learn with the participants of this new practice. The group learning is constituted of the processes of negotiation, sharing and assimilating practical knowledge that take place where the participants share. Thus, learning as a process is indissociable of the exchange of experiences, thoughts, knowledge and meaning. All along the implementation of the project of the inverted classroom, there were several tensions, due to the process of instability generated by change. However, the teachers were able to think of projects on the short and medium term so that the practices were adjusted and negotiated among the teachers themselves, between the teachers and the students, the teachers and the coordination of the course and the coordination of the course and the direction. We conclude that there was the creation of a practice of change and of an identity with a group sense among the four teachers, participants of the new practice. The practice developed new abilities as well as “Knowing in practice” which means that learning contextualized in a practice developed during a collective process which aimed the outcome of a common project made it possible for newcomers to assimilate these new abilities.